2017
DOI: 10.3389/fpsyg.2017.00722
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different LGM-Based Methods with MAR and MNAR Dropout Data

Abstract: The missing not at random (MNAR) mechanism may bias parameter estimates and even distort study results. This study compared the maximum likelihood (ML) selection model based on missing at random (MAR) mechanism and the Diggle–Kenward selection model based on MNAR mechanism for handling missing data through a Monte Carlo simulation study. Four factors were considered, including the missingness mechanism, the dropout rate, the distribution shape (i.e., skewness and kurtosis), and the sample size. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…One common problem with longitudinal study designs is the risk of dropouts, and that these dropouts are not random (e.g., missing due to worsened somatic health or morbidity). Li et al (2017) have suggested that the level of dropouts was the strongest factor for affecting the parameter estimates using the maximum likelihood estimation. In their analyses, level of dropouts could only be ignored if the dropout rate falls below 10%.…”
Section: Statistical Considerationsmentioning
confidence: 99%
“…One common problem with longitudinal study designs is the risk of dropouts, and that these dropouts are not random (e.g., missing due to worsened somatic health or morbidity). Li et al (2017) have suggested that the level of dropouts was the strongest factor for affecting the parameter estimates using the maximum likelihood estimation. In their analyses, level of dropouts could only be ignored if the dropout rate falls below 10%.…”
Section: Statistical Considerationsmentioning
confidence: 99%
“…Mother’s working hours per week were negatively correlated with mother engagement and responsibility, whereas father’s working hours per week and child gender were not correlated with parental involvement. The kurtosis and skewness values for all the variables were lower than 3 (Li et al, 2017), indicating the normal distribution of these variables. The multi-collinearity was identified by the values of variance inflation factor (VIF).…”
Section: Resultsmentioning
confidence: 84%
“…Due to this, data analysis employed selection models for both MAR analysis using maximum likelihood with robust standard errors (MLR) and MNAR using the Diggle-Kenward selection as recommended [50]. Studies have found that the Diggle-Kenward performs better than the MAR based maximum likelihood estimator method under the MNAR mechanism, especially with smaller sample sizes and samples with more than 10% attrition [51]. As the sensitivity analysis showed minimal difference between the MAR and MNAR analyses, only the MAR are reported, and MNAR analyses are available upon request.…”
Section: Missingnessmentioning
confidence: 99%